MOLECULAR DOCKING OF ANTIBACTERIAL ACTIVITY OF HEXAHYDRO-1,2,3-TRIAZINE DERIVATIVES - Tahya, Candra Yulius; Irawati, Wahyu; Karnelasatri, Karnelasatri (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Hexahydro-1,3,5-triazine and its derivatives have piqued the interest of numerous researchers due to its strong biological characteristics, which include antibacterial, antimalarial, fungicidal, antiviral, anticancer, antimicrobial, antiamoebic, anti-inflammatory, and antitubercular effects. The antibacterial activity test in this work was performed using molecular docking on 16 hexahydro-1,3,5-triazine derivative compounds and three drug molecule controls that were selected from the PDB database and targeted Penicillin binding protein 2A (PDB ID: 1VQQ). For docking, Pyrx v.1.1's AutodockVina integration was utilized. Docking utilizing the targeted docking strategy was performed using a specific gridbox that was chosen based on the location of significant amino acids and pharmacological controls. The drug potential of a chemical under test is described by the Pa (Probability to be Active) value. The results of the Pa value analysis showed that several hexahydro-1,3,5-triazine derivative compounds had a higher/better average Pa value compared to the control drugs Ceftaroline and Ceftobiprole. Based on the Lipinski rule of five, the analysis's findings indicated that six out of the sixteen test compounds had good drug-likeness features; however, according to Pfizer, every compound possessed these qualities. Nearly all of the drugs exhibited good pharmacokinetics, according to the ADMET study. According to molecular docking results, 13 out of 16 synthesized compounds generally exhibit a high affinity for the PBP2a target protein. Furthermore, four compounds had a higher affinity than the ceftobiprole drug control when compared to the three drug controls. Synthetic compounds, particularly compounds 7, 16, 15, and 1, have the potential to be used as antibacterial therapies, according to the results of QSAR, ADMET, and docking research.